2010
DOI: 10.4049/jimmunol.0903049
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulatory Properties of Mouse Limbal Stem Cells

Abstract: Stem cells have been demonstrated in nearly all adult mammalian tissues and play a vital role in their physiological renewal and healing after injury. Due to their irreplaceable role in tissue repair, these cells had to develop mechanisms protecting them from deleterious inflammatory immune reactions and ensuring their increased resistance to various apoptosis-inducing agents. In this study, we demonstrate that a population of mouse limbal cells highly enriched for cells expressing markers and charateristics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…1B) and by their capability to inhibit anti-CD3 induced T-cell proliferation (Fig. 1C), consistent with our previous results [27,28]. In addition, we confirmed a specific adipogenic and osteogenic differentiation of MSCs by expression of adipocyte-and osteoblaste-specific markers by real-time PCR (data not shown).…”
Section: Characterization Of Mscssupporting
confidence: 92%
See 1 more Smart Citation
“…1B) and by their capability to inhibit anti-CD3 induced T-cell proliferation (Fig. 1C), consistent with our previous results [27,28]. In addition, we confirmed a specific adipogenic and osteogenic differentiation of MSCs by expression of adipocyte-and osteoblaste-specific markers by real-time PCR (data not shown).…”
Section: Characterization Of Mscssupporting
confidence: 92%
“…Quantitative real-time polymerase chain reaction (PCR) was performed on an iCycler (BioRad, Hercules, CA) as we have previously described [28,29]. The primers used for amplification were as follows:…”
Section: Detection Of Tgf-b and Il-6 Gene Expression By Real-time Polmentioning
confidence: 99%
“…The expression of Fas and FasL in the target cell was reported to be one of the protective mechanisms against lymphocyte attack that promote target cell survival. [33][34][35][36][37][38] Our results showed that there was no significant complement-dependent TDSC lysis. This was consistent with two recent reports that MSCs inhibited complement activation due to the production of factor H and absence of HLA-B.…”
Section: Discussionmentioning
confidence: 55%
“…The first-strand cDNA was synthesized using random primers (Promega, Madison, WI) in a total reaction volume of 25 mL using M-MLV Reverse Transcriptase (Promega). Quantitative real-time PCR was performed in an iCycler (BioRad, Hercules, CA), as previously described [25,26]. The primers used for amplification are shown in Table 1.…”
Section: Detection Of Gene Expression By Real-time Polymerase Chain Rmentioning
confidence: 99%